Ghostwalker : Ghostly Game -Book 19 - Feehan, Christine (New York : Berkley Romance, 2023)
"Sometimes things just go south and there isnt a damn thing you can do about it. Gideon "Eagle" Carpenter eased his body back slowly until he was entirely prone, linked his fingers behind his head and stared up at the stars. This was San Francisco. Viewing stars wasnt always easy because fog liked to creep in at night, at least where he was located. He was on the roof of the four-story, wedged shaped original warehouse made of red bricks that rose like a monstrosity to stand out among all the cool newer concrete and steel warehouses surrounding it. Considering the building was the only one on the street to survive the 1906 earthquake and fires and was still standing despite the city condemning it and threatening to demolish it several times, Gideon thought what others considered an eyesore was worth saving. So, he had saved it. Mostly, for this--the rooftop. He had used every penny of his share of money and then some in order to see to it that the best of the best ensured the old building would withstand anything thrown at it for the next hundred years. "Yeah, Gideon," he repeated aloud. "Shit happens. You roll with it. You dont let it get to you. You come here, high in the sky, and you get rid of it." Because shit did happen in his life far too often. It had been happening since the day he was born, and he was damn sure it would continue to do so until the day he died. Hed created the mantra, found the highest place possible wherever he was, repeated that shit over and over until he made himself to just let the clouds take it all away. They had to take it away. Sometimes, like tonight, when his churning gut was in knots and the devil was riding him hard, he had to call on the universe to shoulder his shit"--
Keywords: Genetic engineering -- Fiction; Psychic ability -- Fiction; Man-woman relationships -- Fiction; Nomads -- Fiction; San Francisco (Calif.) -- Fiction; Romance fiction; Paranormal fiction; Thrillers (Fiction)